Implementation of the AHP Method in Decision Making for Stunting Management at the Sicanang Community Health Center UPT Using a Website - Limbong, Robetauli Febriyanti; Nasution, M. Irfan Aldy (Jurnal ICT : Information and Communication Technologies, 2025)
Stunting remains a persistent public health challenge in Sicanang Village, where socioeconomic disparities and limited access to essential services continue to hinder effective intervention strategies. This study aims to identify and prioritize the key determinants of stunting using the Analytical Hierarchy Process (AHP) to support evidence-based decision-making for targeted interventions. Five criteria were evaluated—stunting prevalence, poor family conditions, maternal education, access to sanitation, and program support—based on expert judgment and field data. The results show that stunting prevalence (31.68%) and poor family conditions (29.43%) are the most influential factors, followed by program support (17.94%), maternal education (10.94%), and sanitation access (9.99%). The Consistency Ratio (0.0107) indicates that the weighting process is methodologically valid. At the sub-district level, Bahari Village and Pulau Bahagia obtained the highest priority scores (3.0161), while Pulau Sicanang ranked lowest (2.6776), highlighting the need for differentiated intervention strategies across locations. These findings underscore the importance of data-driven prioritization to optimize resource allocation, strengthen local health programs, and address the multidimensional determinants of stunting. The study provides a practical framework for policymakers to design targeted, context-specific interventions that can enhance the effectiveness of stunting reduction efforts in vulnerable communities.